Brazilian cherry: identifying local knowledge and diversity of Eugenia involucrata in the countryside of Santa Catarina state/Brazil - Wagner, Julia Goetten; Santos, Karine Louise; Budziak, Dilma; Barbieri, Rosa Lía (Ethnobotany Research and Applications, 2022)
Background: Eugenia involucrata (cerejeira do mato) is a fruit species from the Atlantic Forest Biome, which presents several potential uses; however, it is considered an endangered species. An ethnobotanical survey and physical-chemical evaluations were carried out in order to characterize the local knowledge about E. involucrata, the variability maintained by local communities and identify fruits with agronomic traits of interest. Methods: The study was conducted in the counties of Curitibanos, Frei Rogério, and Rio das Antas. Ethnographic research was used to gather ethnobotanical knowledge. Fruit samples from seven plants owned by family units were evaluated for diameter, height, pH, vitamin C, titratable acidity, and total soluble solids. Results: Nineteen family units were interviewed, where eleven use purposes and fifteen agricultural management practices were mentioned for Eugenia involucrata. The main criteria indicated by people interviewed for E. involucrata selection were “sweeter fruits,” “darker fruits” and “larger fruits.”. There was variability among the seven accessions of E. involucrata evaluated. The accessions 3.D, 4.MI, 5.MII and 6.G were the ones that best met the selection criteria. The affective bond, related to familiar or childhood traditions has contributed to the conservation of E. involucrata. Conclusions: The family units interviewed share a cultural relationship with E. involucrata, which has been perpetuated over generations through the continuous use of the species. Among the genetic variability maintained by the family units, the accessions 3.D, 4.MI, 5.MII and 6.G were those which best attend the selection criteria established. Keywords: cerejeira do Rio Grande, on-farm conservation, ethnobotany.